BEHIND THE BALL: DISCUSSIONS ABOUT GENDER AND WOMEN’S REPRESENTATION IN FUTSAL (Fiep Bulletin - online, 2024)
Introduction: Physical Education and sport, today, are fertile fields for gender discussions, however, they lack studies that specifically address the prejudice relationships that are still recurrent in sports. Situations of prejudice or discrimination are evident in the practice of futsal, for example - thus leading to the study of the approach between gender relations in futsal. Objective: the objective of this article is to analyze the gender relations present in the trajectory of female futsal coaches, seeking to understand which discourses of prohibition surround them. Methods: The research method was chosen using a semi-structured interview that combines closed and open questions, giving the opportunity for wider participation by the interviewees. Results: Among the population of women interviewed, around 74% claim that they have been victims of misogynistic or sexist speeches at work, and when asked if they feel supported or protected by the institution for which they work as coaches, the largest proportion (78%) say no. Conclusion: The low representation of women in management positions in sport is considerably analyzed today – due to the predominance of men occupying coaching roles, confirming the gendered characteristic of sport and its reproduction of social stereotypes about the positions occupied by men and women.
Keywords: Gender; Futsal; Sport